Remix: The art and craft of endless hybridization - Michele Knobel; Colin Lankshear (Journal of Adolescent & Adult Literacy, 2008)
Rinto new kinds of creative blends. Until recently, it mainly referred to us- ing audio-editing techniques to produce “an alternative mix of a recorded song that differed from the original...taking apart the various instruments and components that make up a recording and remixing them into something that sounds completely different” (Seggern, n.d., p. 1). Once digital sound became the norm, all manner of music mixing and sampling techniques were applied using different kinds of hardware devices or software on a computer (Hawkins, 2004). Recently, however, remix has been expanded to include music and sound as well as moving and static images taken from films, televi- sion, the Internet, personal archives, and elsewhere. Lessig (2005) argues that digital remix constitutes a contemporary form of writing on the scale of a mass cultural practice and raises issues demanding serious reform of current copyright law. Here we examine remix as a signifi- cant literacy practice. We explore shifts in everyday writing practices using examples of remix and analyze the art and craft of creating remixes to better understand these practices from insider (and outsider) perspectives. We con- sider some conceptual and theoretical relationships between remix, literacy, and literacy education and conclude with a brief discussion of remix within the context of classroom teaching and learning.
Keywords: adolescence; apprentissage; audio; contexte d'enseignement; création; lecture numérique